Have guidelines addressing physical activity been established in nonalcoholic fatty liver disease? - Finelli, Carmine (Baishideng Publishing Group Co., Limited, 2012)
The purpose of this review was to highlight, in relation to the currently accepted pathophysiology of non-alcoholic fatty liver disease (NAFLD), the known exercise habits of patients with NAFLD and to detail the benefits of lifestyle modification with exercise (and/or physical activity) on parameters of metabolic syndrome. More rigorous, controlled studies of longer duration and defined histopathological end-points comparing exercise alone and other treatment are needed before better, evidence-based physical activity modification guidelines can be established, since several questions remain unanswered.